2013
DOI: 10.1016/j.cell.2013.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Human SNP Links Differential Outcomes in Inflammatory and Infectious Disease to a FOXO3-Regulated Pathway

Abstract: SummaryThe clinical course and eventual outcome, or prognosis, of complex diseases varies enormously between affected individuals. This variability critically determines the impact a disease has on a patient’s life but is very poorly understood. Here, we exploit existing genome-wide association study data to gain insight into the role of genetics in prognosis. We identify a noncoding polymorphism in FOXO3A (rs12212067: T > G) at which the minor (G) allele, despite not being associated with disease susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(222 citation statements)
references
References 60 publications
12
202
0
1
Order By: Relevance
“…Integrative analyses of autoimmune disease genetics have helped to prioritize likely causal genes in GWAS loci, suggesting not only key biological pathways, but perhaps even drug targets and candidate therapies (113). Looking forward, there is hope that such studies will uncover effects of genetic variants that contribute not only to disease risk, but also to heterogeneity in disease progression (114) and responses to therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Integrative analyses of autoimmune disease genetics have helped to prioritize likely causal genes in GWAS loci, suggesting not only key biological pathways, but perhaps even drug targets and candidate therapies (113). Looking forward, there is hope that such studies will uncover effects of genetic variants that contribute not only to disease risk, but also to heterogeneity in disease progression (114) and responses to therapy.…”
Section: Resultsmentioning
confidence: 99%
“…They have been evaluated for association with several diseases including GVHD. [7][8][9][10] Our group has previously shown a risk model using SNPs to predict patients with high risk of developing aGVHD and hence decreased OS. 11 Other studies have also examined SNPs to predict the onset of GVHD, but not their response to steroid therapy or development of SR aGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…We would then like to follow that up with a controlled intervention in two characterised populations, one with the G allele and the other with the wild type, to confirm the effect of the G allele. The minor G allele of FOXO3 has been shown to down-regulate pro-inflammatory cytokines including TNF and to up-regulate the anti-inflammatory cytokine IL-10, which accounts for the less severe symptoms of CD [27]. This reduced inflammatory response may account for the positive association of FOXO3 with tolerance to some foods, but it does not explain why it is associated with an adverse response to other foods.…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al [27] reported that the minor G allele of rs12212067 is associated with less severe symptoms and a less severe course in CD and rheumatoid arthritis, due to the down-regulation of pro-inflammatory cytokines including TNF and the up-regulation of IL-10, an anti-inflammatory cytokine [28,29]. We were interested to consider if this single nucleotide polymorphism also related to dietary intolerances in people with CD.…”
Section: Introductionmentioning
confidence: 99%